International action in favor of democracy in Africa : the Zaire case - (:unkn) unknown (My University, 1999)
This paper proposes an approximation a crucial theme within the consolidation of the democratic regime and the human dignity: the idea of solidarity between Zaire-Congo peoples and other peoples with regard of the democratization of this state. So has the international action in favor of democracy in Africa: the Zaire case is a one within this kind of relationships establish between the performers of the international society with Zaire, but in several levels. This relation could be the co-operation, aid or coaction for the democratization. Really this is an important role assigned in this relationship to these peoples, although through the state. Nowadays, the democratic imperative has been taken into account by the different international performers. This fact has direct consequences on the African state's phenomenon. For this reason, it should be interesting to study the role undertaken by these performers, as well as, the effectiveness of measures taken for the democratization of democratic republic of Congo. Definitively, it is an actual questioning of revising the public law in general and international public law in particular on one hand in relation to its recent evolution, on the other, in trying to resolve the eventual contradictions with contemporary international practice. This practice is characterized by different factors conducting the intervention as well as an international law still dominated by the principle of sovereignty.
Keywords: African Research